Pengaruh Return On Asset, Return On Equity dan Earning Per Share Terhadap Harga Saham pada Sektor Properti yang Terdaftar di BEI Periode 2019 – 2021 - Muhammad Rizal Febriantoro (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The property sector is one of the business instruments usually chosen by investors. This research capital market focuses on the housing construction sector originating from property companies. This company is the same as others, namely buying and selling shares at competitive prices per share. This share buying and selling activity can be dominated by price seasonality criteria when the price of each share rises or falls. Of all types of shares, Property Companies both have low and high return risks. Therefore, risks in the capital market can be predicted using the criteria of Return on Assets, Return on Equity and Earning Per Share. The research was carried out quantitatively by processing secondary data in the form of company financial reports. The research object was property companies registered on the IDX which were then sampled using probability sampling so that 13 companies were found as samples with a research period of 3 years. The method used is Panel Data Regression analysis. The results obtained are partial return on assets, return on equity has a significant positive effect on share prices and earnings per share has a significant negative effect on stock prices. Meanwhile, simultaneously return on assets, return on equity and earnings per share have a positive and significant influence on share prices. The results of the R square test explain that the independent variable is able to explain 84.4% of the variables studied